Risk Factors Affecting the Bacterial Contamination in Water of Thailand’s Upper South 2020 - 2022 - Ruangsombat, Kritsanee; Lim, Apiradee; Pradit, Siriporn; Cholumpai, Varaporn; Noppradit, Prakrit (Trends in Sciences, 2023)
Bacterial contamination in water is an important cause of human health problems. Water-borne infections are among the top 10 reasons for illness in Thailand and accounted for 40 % of all infections necessitating surveillance. The purpose of this study was to identify environmental factors influencing bacterial contamination in water in the upper southern region of Thailand. Secondary data on water quality were obtained from 2 Regional Medical Sciences Centers, and environmental data were collected from the National Statistical Office’s annual reports for 2020 - 2022. A multiple logistic regression model was used to investigate the factors influencing bacterial contamination to exceed the standard. There were 674 water samples contaminated with bacteria, which implied 10.97 % of the total number of samples. The factors that were significantly associated with greater bacterial contamination than standard were provinces and years of production, water types, bacterial types and rainfall levels. Bacteria were more likely to contaminate the water generated in Chumphon province. The quantity contamination for consumption water varied by years of production, with Total Coliform Bacteria (TCB) being the most contaminated bacterial strain as rainfall increases. High precipitation deteriorated biological water quality, which was the origin of water-borne diseases. Entrepreneurs and other connected organizations must constantly watch for bacterial contamination when there is a change in a manufacturing site or when the season changes from hot to rainy. HIGHLIGHTS Environmental changes have an influence on the bacterial contamination of water in Thailand’s upper southern region Rainfall, production location, year of production, types of bacteria, and kinds of water are risk factors related to the presence of bacteria contaminants in water There is greater bacterial contamination in the water as the amount of rainfall increases or rains more Indicator bacteria are more easily detected in water than disease bacteria Bacteria are more likely to be detected in processed water and household water than in drinking water and ice for consumption GRAPHICAL ABSTRACT